Phylogenetic Inference on Limnonectes kuhlii Complex in Java and Sumatra Reveals Significant Novel Diversity - Fahmi, Muhamad; Kadafi, Ahmad Muammar; Priambodo, Bagus; Fauzi, Muhammad Alif; Hamidy, Amir; Firdaus, Anggun Sausan; Smith, Eric Nelson; Kurniawan, Nia (Graduate School, Universitas Brawijaya, 2023)
The fanged frog, Limnonectes kuhlii, exemplifies the complexity of cryptic species. Though originally described from Java, subsequent studies indicate that L. kuhlii encompasses multiple lineages, suggesting the presence of several undescribed species. Suspecting the existence of multiple undescribed species within the L. kuhlii complex in Sumatra, we collected 17 specimens from Java and Sumatra. We extracted the 12S, tRNAval, and 16S mitochondrial DNA from these specimens for phylogenetic analysis using Maximum Likelihood and Bayesian Inference methods and for estimating time divergence. Our findings uncovered two novel diversity within the L. kuhlii complex both in Sumatra and Java. Furthermore, our estimation of time divergence suggests that the diversification of L. kuhlii in Java and Sumatra was influenced by geological and climatic events, including landmass emergence and sea-level fluctuations. In conclusion, our research provides critical insights into the evolutionary complexity and diversity of the L. kuhlii complex in Sumatra and Java. While our molecular evidence suggests novel diversity, further comprehensive morphological studies are imperative to confirm and describe these potential new species. Furthermore, additional sampling across its range and deeper investigations integrating both molecular and morphological data are crucial. Keywords: fanged frogs, Limnonectes kuhlii, Limnonectes sisikdagu, phylogenetics.